Interference Effect of Prior Explicit Information on Motor Sequence Learning in Relapsing-Remitting Multiple Sclerosis Patients - Zahiri, N.; Abollahi, I.; Nabavi, S.M.; Ehsani, F.; Arab, A.M.; Shaw, I.; Shariat, A.; Shaw, B.S.; Dastoorpoor, M.; Danaee, M.; Sangelaji, B. (Penerbit Universiti Sains Malaysia, 2017)
Background: Multiple sclerosis (MS) is the most widespread disabling neurological condition in young adults around the world. The purpose of this study was to investigate the impact of explicit information (EI) on motor-sequence learning in MS patients. Methods: Thirty patients with relapsing-remitting MS (RRMS), age: 29.5 (SD = 5.6) years and 30 healthy gender-, age-, and education-matched control group participants, age: 28.8 (SD = 6.0) years, were recruited for this study. The participants in the healthy group were then randomly assigned into an EI (n = 15) group and a no-EI (n = 15) group. Similarly, the participants in the control group were then randomly assigned into EI (n = 15) and no-EI (n = 15) groups. The participants performed a serial reaction time (SRT) task and reaction times. A retention test was performed after 48 hours. Results: All participants reduced their reaction times across acquisition (MS group: 46.4 (SD = 3.3) minutes, P < 0.001, and healthy group: 39.4 (SD = 3.3) minutes, P < 0.001). The findings for the within-participants effect of repeated measures of time were significant (F(5.06, 283.7) = 71.33. P < 0.001). These results indicate that the interaction between group and time was significant (F(5.06, 283.7) = 6.44. P < 0.001), which indicated that the reaction time in both groups was significantly changed between the MS and healthy groups across times (B1 to B10). The main effect of the group (MS and healthy) (F(1, 56) = 22.78. P < 0.001) and also the main effect of no-EI vs EI (F(1, 56) = 4.71. P < 0.001) were significant. Conclusion: This study demonstrated that that RRMS patients are capable of learning new skills, but the provision of EI prior to physical practice is deleterious to implicit learning. It is sufficient to educate MS patients on the aim and general content of the training and only to provide feedback at the end of the rehabilitative session.